Management of asymptomatic stage IV rectal cancer: should the primary tumor be resected? - Faisal, Elagili; Stocchi, Luca; Kalady, Matthew F; Dietz, David (Wiley-Blackwell, 2014)
Aim: The need for resection of the primary tumour in stage IV minimally symptomatic rectal cancer (RC) is controversial.